Young men's talk about menstruation and hegemonic masculinity in the South African context: a discursive analysis - Glover, Jonathan M (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
Current research in the sub-Saharan and other resource poor contexts indicates the largely negative social constructions of menstruation and menstruating women. Young men have been shown to reproduce these negative constructions and reinforce the stigmatized status of menstruation in these contexts. To my knowledge no studies have examined the ways in which young men talk about menstruation and menstruating women in South Africa. In this research, I aimed to explore the ways in which young men (in a resource poor area in the Eastern Cape) talk about menstruation in with their male peers in a focus group context and how this talk serves to enable specific subject positions (both masculine and feminine) that may reproduce, comply with and resist constructions of hegemonic masculinity (as outlined in previous South African research). By drawing on Raewyn Connell's influential framework of masculinities and augmenting this with Margaret Wetherell and Nigel Edley's contributions, this research adds to the growing body of research on masculinities in the South African context. I utilized a discursive framework in which to understand the interpretative repertoires drawn on in everyday talk about menstruation and the specific subject positions made available by these. Purposive sampling was used to recruit a total of 37 participants from two former Department of Education and Training schools in the Eastern Cape. Participants were young 'black' men with a mean age of 18.3 In analyzing and interpreting the data two overarching patterns emerged. In the first, the participants discursively distanced themselves from menstruation (and femininity in general) in order to avoid possible marginalisation and subordination in relation to local hegemonic masculine ideals. In doing this, the participants drew on a number of interpretative repertoires including: a dualistic repertoire, a bad (versus ideal) femininity repertoire and an abject femininity repertoire, which assisted in creating numerous subject positions. These subject positions allowed the young men to align themselves closer to hegemonic masculine ideals, and create distance by positioning menstruating women as the 'other'. In the second overarching pattern, menstruation was constructed as a threat to masculine identity; within this construction, the young men discursively negotiated the ideological dilemmas surrounding this 'highly feminine' topic in ways that bolstered their positions within the gender hierarchy. Overall, hegemonic masculinities in this context were discursively reproduced and complied with in the participants' accounts.
Keywords: Menstruation -- Social aspects -- -- South Africa -- Eastern Cape; Hegemony -- South Africa -- Eastern Cape; Masculinity -- South Africa -- Eastern Cape; Sex role -- South Africa -- Eastern Cape; Men -- Attitudes; Men -- Psychology; Human body -- Social aspects -- South Africa -- Eastern Cape; Men's studies -- South Africa -- Eastern Cape